Acoustic filters with two perforated tubes - BRZÓZKA, G. (Archives of Acoustics, 1991)
This paper presents a physical and mathematical model of a filter. It was built on the basis of segmentation of its components and description of acoustic properties of these components with a transmission matrix. Also formulae for calculating transmission matrices for many specific solutions of the filter have been given in a convenient and generalized form. The presented model is limited to: the conditions of propagation of a harmonic plane acoustic wave, small dimensions of the holes in the perforation and laminar flow through these holes.